The role of isolated diffuse axonal brain injury on post-traumatic depressive- and anxiety-like behavior in rats - Anna Oleshko; Benjamin F. Gruenbaum; Vladislav Zvenigorodsky; Ilan Shelef; Shahar Negev; Igor Merzlikin; Israel Melamed; Alexander Zlotnik; Amit Frenkel; Matthew Boyko (Translational Psychiatry)
Abstract Traumatic brain injury (TBI) is a significant global health concern and is associated with short-term and long-term comorbidities such as mood disorders and reduced quality of life. Diffuse axonal brain injury (DABI) is a common but severe type of TBI. The role of DABI in the development of psychiatric sequelae after TBI is not well understood due to the challenge of isolating DABI from general TBI in the human population. Here we investigate the role of DABI in the occurrence of post-TBI depressive- and anxiety-like behaviors in a rat model. Forty rats were randomly assigned to two groups, with 20 receiving DABI and 20 receiving sham treatment. We used a magnetic resonance imaging (MRI) protocol developed for DABI using a 3-T clinical scanner to confirm DABI. We then compared neuroimaging, neurological and behavioral assessments across experimental groups. There was a significant difference between DABI and sham groups on sucrose preference, a measurement of depressive-like behavior (p < 0.012), and time spent on open arms on a plus maze test, a measurement of anxiety-like behavior (p < 0.032). For MRI-detected injury, there was a difference in diffusion-weighted imaging with relative anisotropy (p < 0.001) and fractional anisotropy (p < 0.001) mapping. We found that isolated DABI in our model led to post-traumatic depressive-like behavior in 30% of cases and anxiety-like behavior in 35%. Additionally, we established diagnostic cut-offs for depressive-like and anxiety-like behaviors in injured rats. We also documented comorbidity between the development of depression and anxiety in DABI-exposed rats. We anticipate that this study will greatly enhance the understanding of the relationship between DABI, TBI, and mood disorders like depression and anxiety, and aid in developing treatment options for these interconnected conditions.